Indian resilience and rebuilding : Indigenous nations in the modern American west - Fixico, Donald Lee, 1951- (Tucson : The University of Arizona Press, 2013)
This book's exploration of Native resilience in the twentieth century demonstrates how Native Americans reinvented themselves, rebuilt their nations, and ultimately became major forces in the United States. -- Adapted from publisher's description.
Introduction : Rebuilding Nations and the Indian Problem : Why Does It Matter? -- Resilience. Reservation Life and Land Allotments : Adaptation to New Homelands ; Missionaries and Boarding Schools : Education as a Tool ; The Indian New Deal and Tribal Governments : Flexibility of Adaptation ; Relocation and Urban Indian Communities : Navigating Cultural Systems -- Rebuilding. Red Power Activism, the American Indian Movement, and Wounded Knee : The Rise of Modern Indian Leadership ; Political Economy and Tribal Natural Resources : Resource Management ; Indian Gaming in the West : Indian Entrepreneurship and Modern Political Economy ; Sacred Land Returns and Repatriation : Power of Federal Indian Law -- Conclusion : Resilience, Rebuilding Nations, and Problem Solved : It Does Matter.
Includes bibliographical references (pages 224-269) and index.
Description based on online resource; title from digital title page (viewed on December 18, 2024).
JSTOR
Keywords: Indians of North America -- Historiography; Indians of North America -- Government relations; Indians of North America -- Politics and government; Self-determination, National -- United States; United States -- Historiography; Droit des peuples à disposer d'eux-mêmes -- États-Unis.; Peuples autochtones -- États-Unis -- Relations avec l'État.; SOCIAL SCIENCE -- General; Historiography; Indians of North America -- Government relations; Indians of North America -- Historiography; Indians of North America -- Politics and government; Self-determination, National; United States